Streamlining Medical Services: A Virtual Chatbot for Stomach- related Illnesses - Tresna Maulana Fahrudin; Angela Lisanthoni; Prismahardi Aji Riyantoko; Kartika Maulida Hindrayani; Dwi Arman Prasetya (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The stomach is an important part of the digestive system as it stores and breaks down food for the body’s energy. In Indonesia, some people engage in dense work activities but eat late, which can lead to stomach problems. The younger generation often consumes high-fat and junk foods, increasing their risk of stomach-related. Raising public awareness through social media platforms about the various stomach illnesses, including symptoms, risks, and treatments, is important. To achieve this, a chatbot called "A.L.T.H.A" has been proposed to provide information on diseases related to the stomach, utilizing Google Dialogflow and third-party applications, it’s programmed to understand different intents, actions, parameters, and entities, and respond appropriately to user queries. The chatbot was tested on 10 end-users and successfully provided relevant information on different stomach-related issues, including welcome, fallback, main, also closing intents.